155k views
4 votes
How would you solve #12?

How would you solve #12?-example-1
User Ronnette
by
5.6k points

1 Answer

3 votes

You can use the difference of square equation:


a^2-b^2 = (a+b)(a-b)

In fact,
x^4 is the square of
x^2 and
a^4 is the square of
a^2

This means that you can write
x^4-a^4 = (x^2+a^2)(x^2-a^2)

So, the denominator simplifies:


(x^4-a^4)/(x^2-a^2) = ((x^2+a^2)(x^2-a^2))/(x^2-a^2) = x^2+a^2

So, when
x \to a, obviously
x^2 \to a^2, and the limit is simply


\displaystyle \lim_(x \to a) (x^4-a^4)/(x^2-a^2) = \lim_(x \to a) x^2+a^2 = a^2+a^2 = 2a^2

User Shortduck
by
5.7k points